2008
DOI: 10.1074/jbc.m710584200
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Secretory Phospholipase A2 Group X Enhances Anti-inflammatory Responses, Promotes Lipid Accumulation, and Contributes to Aberrant Lung Pathology

Abstract: Secreted phospholipase A2 group X (sPLA 2 -X) is one of the most potent enzymes of the phospholipase A 2 lipolytic enzyme superfamily. Its high catalytic activity toward phosphatidylcholine (PC), the major phospholipid of cell membranes and lowdensity lipoproteins (LDL), has implicated sPLA 2 -X in chronic inflammatory conditions such as atherogenesis. We studied the role of sPLA 2 -X enzyme activity in vitro and in vivo, by generating sPLA 2 -X-overexpressing macrophages and transgenic macrophage-specific sPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 39 publications
4
55
0
Order By: Relevance
“…We also incubated peritoneal macrophages from PLA2G10 Tg mice (22) with LDL and found that these cells also accumulated oil red O-stained lipid droplets (Fig. 6D), confirming that PLA2G10-exposed LDL facilitates macrophage foam cell formation, as reported previously (23,31,34). After treatment with Ac-LDL, formation of foam cells from macrophages of all genotypes was obvious (Fig.…”
Section: Pla2g3-treated Ldl Facilitates Macrophage Foam Cell Formatiosupporting
confidence: 59%
See 1 more Smart Citation
“…We also incubated peritoneal macrophages from PLA2G10 Tg mice (22) with LDL and found that these cells also accumulated oil red O-stained lipid droplets (Fig. 6D), confirming that PLA2G10-exposed LDL facilitates macrophage foam cell formation, as reported previously (23,31,34). After treatment with Ac-LDL, formation of foam cells from macrophages of all genotypes was obvious (Fig.…”
Section: Pla2g3-treated Ldl Facilitates Macrophage Foam Cell Formatiosupporting
confidence: 59%
“…In our ongoing effort to gain new insights into the in vivo functions of sPLA 2 enzymes, in this study we established and analyzed Tg mice for PLA2G3, an atypical mammalian sPLA 2 structurally more similar to bee venom PLA 2 than to other mammalian sPLA 2 s. PLA2G3 Tg mice did not display noticeable phenotypic changes in the skin, which is profoundly affected in PLA2G2A mice (24), or lung, whose architecture is disrupted in PLA2G5 Tg mice (22) and macrophage-specific PLA2G10 Tg mice (23), suggesting that phospholipids in mouse skin and lung surfactant may not be main targets for PLA2G3 in vivo. However, we have obtained evidence that PLA2G3 can target phospholipids in plasma lipoproteins in vivo, leading to a decrease in HDL and an increase in modified and aggregated LDL, which are risk factors for atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Further study using model systems with selective PLa2g10 deficiency in epithelial cells and macrophages will be needed to resolve the relative importance of each of these cell types in animal models, because the development of airway inflammation and AHR is impaired with global PLa2g10 deficiency (21,22). Although transgenic expression of full-length PLA2G10 in mice is not associated with pathology in the absence of inflammation (40), the transgenic expression of active PLA2G10 without the propeptide sequence in macrophages causes significant lung dysfunction related to the degradation of surfactant phospholipids (41). Thus, macrophage expression of PLA2G10 could alternatively be an important source of sPLA 2 -X in the airways.…”
Section: Discussionmentioning
confidence: 99%
“…GX KO mice exhibit significantly reduced myocardial infarct size in response to ischemia/reperfusion injury, which has been attributed to attenuated neutrophil cytotoxic activities (18). Transgenic macrophage-specific expression of the mature form of human GX sPLA 2 results in fatal pulmonary defects in mice suggesting an involvement of GX sPLA 2 in inflammatory lung diseases (19).…”
mentioning
confidence: 99%